SENSORY EVALUATION OF YOGURT IN VARIOUS SUGAR CONCENTRATION - Wardha Maulidya Pratiwi; Firda Nasrulia; Jelita Zahra Aprillia; Ghea Dionita Sanora; Ismi Nurul Kartika (Food ScienTech Journal, 2020)
The purpose of this study was to determine the hedonic test of various concentrations of sugar in UHT milk with the help of Lactobacillus casei in making yogurt on the color, aroma, taste, and thickness of the resulting yogurt. In this study, there are treatment factors, namely the concentration of granulated sugar. The results showed that the concentration of sugar affects the color, aroma, taste, and thickness of the resulting yogurt. In the hedonic test, the results were observed that in each provision of sugar found a difference in values obtained.